Long-term follow-up after rituximab for steroid-dependent idiopathic nephrotic syndrome - Kemper, Markus J.; Gellermann, Jutta; Billing, Heiko (Nephrology, dialysis, transplantation, 2012)
Abstract Background.. In patients with refractory steroid-sensitive nephrotic syndrome (SSNS), treatment with rituximab has shown encouraging results; however,